2015
DOI: 10.1371/journal.pone.0126771
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis between the Cytoplasmic Male Sterile Line NJCMS1A and Its Maintainer NJCMS1B in Soybean (Glycine max (L.) Merr.)

Abstract: BackgroundThe utilization of soybean heterosis is probably one of the potential approaches in future yield breakthrough as was the situation in rice breeding in China. Cytoplasmic male sterility (CMS) plays an important role in the production of hybrid seeds. However, the molecular mechanism of CMS in soybean remains unclear.ResultsThe comparative transcriptome analysis between cytoplasmic male sterile line NJCMS1A and its near-isogenic maintainer NJCMS1B in soybean was conducted using Illumina sequencing tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(64 citation statements)
references
References 48 publications
10
54
0
Order By: Relevance
“…Unfortunately, currently-available microarray and RNA-seq data are mainly for flowers, anthers, or pollen grains [37][38][39][40]. However, these studies indicated that functions of pollen-enriched genes and differentially expressed genes in the male-sterile mutants are mainly relative to two pathways: cell wall and cytoskeletal remodeling [37,40], highlighting possible roles for these genes in pollen wall development. Furthermore, our recent genome-wide coexpression analysis revealed that 98 candidate genes with specific expression in the anther are likely involved in pollen wall formation.…”
Section: Tryphine Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, currently-available microarray and RNA-seq data are mainly for flowers, anthers, or pollen grains [37][38][39][40]. However, these studies indicated that functions of pollen-enriched genes and differentially expressed genes in the male-sterile mutants are mainly relative to two pathways: cell wall and cytoskeletal remodeling [37,40], highlighting possible roles for these genes in pollen wall development. Furthermore, our recent genome-wide coexpression analysis revealed that 98 candidate genes with specific expression in the anther are likely involved in pollen wall formation.…”
Section: Tryphine Formationmentioning
confidence: 99%
“…Furthemore, mutation in genes encoding other polysaccharide-associated enzymes also causes abnormal pollen wall development [31,32,36]. Recent transcriptomic analyses also indicated that the expression of polysaccharide metabolism-associated genes in a male-sterile soybean line was significantly downregulated compared to the male-fertile line; these genes encode invertases, hexokinases, and pectin lyases [37]. However, little is known about the biochemical mechanism.…”
Section: Conservation and Diversification Of Genes/enzymes Involved Imentioning
confidence: 99%
“…Mainly, TFs act by binding the cis element present inside the transcription initiation (promoter) region of their target gene [15]. Recent studies have shown that changes in gene expression are closely related with changes in expression of TFs [16] affecting growth and development in plants [17]. Manipulation of desired traits in plants by engineering TF genes is considered as a major future outlook [18].…”
Section: Regulatory Roles Of Transcription Factors In Plantsmentioning
confidence: 99%
“…To elucidate the mechanism of MS more comprehensively, the transcriptomes of many higher plants have been sequenced, including Arabidopsis [21], buckwheat [22], cotton [2325], watermelon [26], soybean [27], Brassica napus [2830] and Brassica oleracea [31]. In this study, fertile and sterile flower buds from DGMS line with a length of ~2.5 mm were sampled for RNA-seq, representing the first study of the sesame DGMS transcriptome.…”
Section: Introductionmentioning
confidence: 99%